Situation Report: Romania, 24 May 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Architects to the US Albanian-Romanian Agreement on Consumer Cooperatives Soviet Composers to Romania Red Cross Delegation to Moscow Central Committee Message on Art Polish-Romanian Technical-Scientific Cooperation Reaction to Sino-North Vietnamese Communiqué Miscellaneous